Comparison of Diagnostic Accuracy of Thyroid Cancer With Ultrasound-Guided Fine-Needle Aspiration and Core-Needle Biopsy: A Systematic Review and Meta-Analysis - Lan, Ling; Luo, Yong; Zhou, Meicen; Huo, Lili; Chen, Hailing; Zuo, Qingyao; Deng, Wei (Frontiers in Endocrinology, 2020)
This systematic review and meta-analysis aimed to evaluate the accuracy of fine-needle aspiration (FNA) and core-needle biopsy (CNB) in diagnosing thyroid cancer. The PubMed, Embase, and Cochrane Library databases were retrieved up to May 2019, and the overall accuracy of FNA and CNB in diagnosing thyroid cancer was evaluated by meta-analysis. The sensitivity, specificity, positive likelihood ratio (PLR), and negative likelihood ratio (NLR) were calculated. The summary receiver operating characteristic (ROC) curve was estimated, and the area under the ROC curve (AUC) was calculated. Ten eligible studies, involving 10,078 patients with 10,842 thyroid nodules, were included. The overall sensitivity and specificity of FNA and CNB for thyroid cancer were 0.72 [95 % confidence interval (CI): 0.69–0.74], 0.99 (95 % CI: 0.98–0.99) and 0.83 (95 % CI: 0.81–0.85), 0.99 (95 % CI: 0.98–0.99), respectively. Other parameters used to assess efficacy included PLR 41.71 (2.15–808.27) and 51.56 (3.20–841.47), NLR 0.31 (0.22–0.42) and 0.22 (0.15–0.32), for FNA and CNB, respectively. Overall, the pooled summary ROC (AUC) value of FNA and CNB was 0.9025 and 0.7926, respectively. No significant difference was observed between the two AUCs of FNA and CNB (P = 0.164). FNA and CNB are still similar as first-line diagnostic tools. FNA remains a good first-line method for detecting thyroid malignancies.